2021
DOI: 10.1186/s12891-021-04048-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between treatment goals, patient characteristics, and outcome measures for patients with musculoskeletal disorders in physiotherapy practice

Abstract: Background Goal setting is linked to person-centred care and is a core component in physiotherapy, but the associations between goal classes, patient characteristics and outcome measures for musculoskeletal disorders has not been investigated. The study’s purpose was to examine 1) how goals used in clinical practice for patients with musculoskeletal disorders (MSD) are distributed in classes based on ICF, 2) if goal classes were associated with patient characteristics and 3) whether goal classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…However, the perception of a poor prognosis is often linked to a decline in an individual's ability to complete ADLs. Setting goals linked to activity participation and functional ability has been linked to patient‐centred care and improvements in outcomes in the management of MSDs (Amundsen et al., 2021). Therefore, when setting goals, physiotherapists may wish to consider targeting leisure activities to frame goals in a positive way and motivate individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the perception of a poor prognosis is often linked to a decline in an individual's ability to complete ADLs. Setting goals linked to activity participation and functional ability has been linked to patient‐centred care and improvements in outcomes in the management of MSDs (Amundsen et al., 2021). Therefore, when setting goals, physiotherapists may wish to consider targeting leisure activities to frame goals in a positive way and motivate individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Patients seeking health care for chronic musculoskeletal (MSK) pain report problems with a variety of everyday life health domains that includes physical activity, vitality, mental well-being, sleep, work, and social relationships [ 1 4 ]. They also report a wide range of goals for treatment, and it is shown that goals set by patients with low back pain included a mixture of health domains [ 3 , 5 , 6 ]. In response to these challenges, a set of core outcome measures covering a range of health domains including pain, disability, and health-related quality of life (HRQoL) have been suggested [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Without communication and coordination, isolated efforts to rehabilitate the stroke survivor are unlikely to achieve their full potential." It is recommended that patient assessment in stroke rehabilitation be based on the International Classification of Functioning, Disability and Health [11]. Therefore, family information, such as family caregiving abilities and home environment, is useful for medical workers.…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines for adult stroke rehabilitation published by the American Heart Association/American Stroke Association [ 10 ] indicate that “Communication and coordination between a large team, including the patient and his or her families, physicians, nurses, physical and occupational therapists, speech-language pathologists [is] paramount in maximizing the effectiveness and efficiency of rehabilitation. Without communication and coordination, isolated efforts to rehabilitate the stroke survivor are unlikely to achieve their full potential.” It is recommended that patient assessment in stroke rehabilitation be based on the International Classification of Functioning, Disability and Health [ 11 ]. Therefore, family information, such as family caregiving abilities and home environment, is useful for medical workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation